Impact of sodium butyrate on the network of adhesion/growth-regulatory galectins in human colon cancer in vitro - Katzenmaier, Eva-Maria Katharina; André, Sabine; Kopitz, Jürgen; Gabius, Hans-Joachim (Anticancer research, 2014)
Background/Aim: The physiological compound sodium butyrate can induce differentiation in colon cancer cells in vitro. Due to the role of galectins in growth control we explored its effect on this network beyond galectins-1 and -3, with deliberate consideration of the status of microsatellite stability, for nine cell lines. Materials and Methods: Microscopical monitoring and measurement of alkaline phosphatase activity ascertained butyrate's impact on cells. Monitoring by reverse transcriptase-polymerase chain reaction (RT-PCR) and western blotting with galectin-type-specific probes characterized galectin expression. Results: Controlled by expectable strong up-regulation of galectin-1 and comparatively small effects on galectin-3 regulation for galectins-4, -7, -8 and -9 were reported with no obvious association to microsatellite stability status. Neoexpression of the GAL-12 gene was observed in eight out of nine tested lines. Conclusion: Butyrate affects the galectin network beyond galectins-1 and -3, warranting further cell biological and histochemical studies.